FENOMENA ULAT BULU DALAM KARYA LUKIS - REHAN OSSA, Yasrul Sami, S.Sn, M.Sn, Drs. Idran Wakidi (Serupa The Journal of Art Education, 2014)
The caterpillar is a kind of small animal, having fur and unique that is verycomplained by the human being especially the farmers, that the caterpillar is thegreedy pest eating the leaves so that the farmers are inflicted a financial loss. Thewriter thinks that the caterpillar which is inflict a financial loss for the human is a symbol of the bad attitude of human and inflict a financial loss for the other human. The work that will be made presenting the caterpillar object, as the parable of the greedy humans characteristic and never satisfied. From these main idea will be developed into ten titles of painting work, such as: 1). Becoming an epidemic, 2). The preys, 3). The authoritys, 4). The apple (AS), 5). The import meat, 6). The corruption policeman, 7). Saving, 8). Century, 9). The leader candidate , 10). The verdict.This last work is climed to enlarge the knowledge about the caterpillar andthe symbols in this last work. This work is visualization based on the up to date phenomenon into the painting work by using decorative realist style.Then in this last work the writer prefers the caterpillars object from manykind as the main symbol. Meanwhile for the writers work doesnt fill. The empty space very much into the background and the colour for the writers background is more equalized than the object in order to the main object aesthetics is more focused. Kata kunci: Ulat bulu simbol sikap manusia yang berprilaku buruk